Reagan's path to victory the shaping of Ronald Reagan's vision ; selected writings - Reagan, Ronald 1911-2004 (Free Press, 2004)
Presents a comprehensive chronology of over three hundred of Ronald Reagan's public addresses where he reacted to the events surrounding the Carter administration, argued against the Panama Canal treaties, detente with the Soviet Union, and taxes, and includes an audio CD of twenty original radio addresses.
Includes index.
Keywords: Reagan, Ronald -- Political and social views; Reagan, Ronald -- 1911-2004; USA -- Government; Geschichte 1974-1981; Politik; USA; United States -- Politics and government -- 1974-1977; United States -- Politics and government -- 1977-1981; Aufsatzsammlung